Pay for performance and contractual choice: The case of general practitioners in England - Eleonora Fichera; Mario Pezzino (Health Economics Review, 2017)
The Quality and Outcomes Framework (QOF) is a Pay-for-Performance scheme introduced in England in 2004 to reward primary care providers. This incentive scheme provides financial incentives that reward the overall performance of a practice, not individual effort. Consequently, an important question is how the QOF may affect contractual choices, quality provision and doctor mobility in the primary healthcare labour market. The paper provides a simple theoretical model that shows that the introduction and further strengthening of the scheme may have induced practices to compete for the best doctors and modified their choices in terms of contractual agreements with practitioners. We test the implications of this model using a linkage between Doctors Census data and practices' characteristics from 2003 to 2007. We use linear multilevel models with random intercept and we account for sample selection. We find that after the introduction of the QOF efficient doctors are more likely to become partners and mobility among doctors has increased. The strengthening of the scheme in 2005 is associated with an increase in the quality of primary care and a reduction in access to the market for new doctors.
Keywords: I11; I18; J41; 330; P4P; contracts; Primary care; Mobility